Phase II study of durvalumab monotherapy in patients with previously treated microsatellite instability‐high/mismatch repair‐deficient or POLE‐mutated metastatic or unresectable colorectal cancer. Issue 12 (1st March 2022) - Oh, Chung Ryul; Kim, Jeong Eun; Hong, Yong Sang; Kim, Sun Young; Ahn, Joong Bae; Baek, Ji Yeon; Lee, Myung‐Ah; Kang, Myoung Joo; Cho, Sang Hee; Beom, Seung‐Hoon; Kim, Tae Won
Abstract: The aim of our study is to evaluate the clinical efficacy of durvalumab in patients with microsatellite instability‐high/mismatch repair‐deficient (MSI‐H/dMMR) or polymerase epsilon ( POLE )‐mutated metastatic or unresectable colorectal cancer (mCRC) who had disease progression after standard chemotherapy. This prospective, open‐label, multicenter, phase II study enrolled patients with mCRC harboring MSI‐H/dMMR or POLE mutations treated with at least one prior line of therapy. The participants received durvalumab (1500 mg) every 4 weeks intravenously. The primary endpoint was the objective response rate (ORR). Of the 33 patients, 30 had MSI‐H/dMMR and 3 had POLE ‐mutated microsatellite stable (MSS) CRC. With a median follow‐up duration of 11.2 months (95% confidence interval [CI]: 7.3‐15.0), the ORR was 42.4% (95% CI: 25.5‐60.8). Among three patients with POLE ‐mutated CRC, one patient who had an exonuclease domain mutation (EDM) achieved an objective response, but the others with mutations in the non‐exonuclease domain had progressive disease. Overall, the median duration of response was not reached and 85.7% of the responses were ongoing at data cutoff. The progression‐free survival rate of 12 months was 58.2% (95% CI: 39.0‐73.1) and the 12‐month overall survival rate was 68.3% (95% CI: 48.8‐81.7). Grade 3 treatment‐related adverse events occurred in 36.4% of the patients and were manageable. In conclusion, durvalumab showed promising clinical activity with encouraging response rates and satisfactory survival outcomes in mCRC patients with MSI‐H/dMMR or POLE EDM. In patients with POLE ‐mutated mCRC, clinical response to durvalumab may be restricted to those with EDM. Abstract : What's new? Tumor mutational burden can predict the efficacy of immune checkpoint inhibitors in various types of cancer. Here, the authors performed a prospective, open‐label, multicenter, phase II trial evaluating the efficacy of the anti‐PD‐L1 monoclonal antibody, durvalumab in patients with metastatic or unresectable colorectal cancer harboring MSI‐H/dMMR or POLE ‐mutations treated with at least one prior line of chemotherapy. Durvalumab showed encouraging anti‐tumor activity with tolerable toxicity in these patient groups. The results provide clinical evidence that an anti‐PD‐L1 agent could be a reasonable option in the treatment of metastatic or unresectable colorectal cancer patients with MSI‐H/dMMR or POLE mutations.